2020
DOI: 10.3390/ijms21103566
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Genes Involved in Axon Guidance: How Much Have We Learned?

Abstract: Neuronal axons are guided to their target during the development of the brain. Axon guidance allows the formation of intricate neural circuits that control the function of the brain, and thus the behavior. As the axons travel in the brain to find their target, they encounter various axon guidance cues, which interact with the receptors on the tip of the growth cone to permit growth along different signaling pathways. Although many scientists have performed numerous studies on axon guidance signaling pathways, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 176 publications
(247 reference statements)
0
13
0
Order By: Relevance
“…GO analysis showed that the target genes of WT1-AS were enriched in actin binding, indicating it regulates the gene expression of proteins that bind actin and thereby potentially modulates the properties and/or functions of the actin filament. Axon guidance, a significantly enriched pathway found by KEGG analysis, allows the formation of intricate neural circuits that favor axons to form synaptic connections (Russell & Bashaw, 2018;Kim & Kim, 2020). Studies have shown that disrupted axon guidance contributes to neurological disorders (Niftullayev & Lamarche-Vane, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…GO analysis showed that the target genes of WT1-AS were enriched in actin binding, indicating it regulates the gene expression of proteins that bind actin and thereby potentially modulates the properties and/or functions of the actin filament. Axon guidance, a significantly enriched pathway found by KEGG analysis, allows the formation of intricate neural circuits that favor axons to form synaptic connections (Russell & Bashaw, 2018;Kim & Kim, 2020). Studies have shown that disrupted axon guidance contributes to neurological disorders (Niftullayev & Lamarche-Vane, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Axon guidance is essential for intricate neural circuit formation in brain development [ 72 ]. Some studies have shown an abnormal expression or mutation of axon guidance–related genes or proteins that are indispensable for maintaining normal synaptic structure and connections in adults, and are associated with different neurological disorders [ 72 , 73 ], such as AD, PD, autism spectrum disorder (ASD), amyotrophic lateral sclerosis as well as other diseases. For example, netrin-1 plays a protective role against AD and may be a potential target for AD [ 74 , 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…Axon guidance molecules combined with their receptors properly guide the axon to its target to form specific synaptic connections during the development of brain regions, such as the hippocampus ( Skutella and Nitsch, 2001 ; Kim and Kim, 2020 ). Aberrant expression of the axon guidance system can lead to brain disorders, and thus impact behaviors ( Van Battum et al, 2015 ; Zhang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%